Simulation on Network Security Design Architecture for Server Room in Rwanda Information Technology Agency - Eric, Karerangabo (2009)
Today, computer networks attacks have continued to increase in severity and sophistication. Data lost and unavailability of network resources due to attacks from internet have negative financial impact on many companies. Unprotected organisation’s networks from internet attacks face high risk of data loss and espionage. Network devices that make up network are the most targeted in order to penetrate in companies system as some come with vulnerability from the manufacturer. In this study, network security architecture for server room had been developed for enhancing the security. Further, two simulation models had been developed to compare the throughput for both existing and developed security architecture.